Soft magnetic properties of patterned Co-based amorphous wires with various dimensions - Park, Chang Bean; Kim, Do Hun; Chun, Dong Won; Han, Jun Hyun; Choi, Heon Jin; Jeung, Won Young (PHYSICA STATUS SOLIDI C - CURRENT TOPICS IN SOLID STATE PHYSICS, VOL 4, NO 12, 2007)
Soft magnetic properties of melt spun Co-based amorphous wires fabricated by photo lithography and wet etching processes were examined with length ( 1 similar to 10 Him), width ( 200 mu m similar to 6 mm), and thickness ( 3 similar to 20 mu m) variation. The value of coercivity H-c, susceptibility K and squareness were extracted from M-H curve measured using a vibrating sample magnetometer (VSM). Monotonic increase of these values with aspect ratio of the wires was observed, which shows that the magnetic properties of the samples were largely determined by shape anisotropy. The observed phenomena were explained by the competition between domain wall pinning and demagnetizing field. It was shown that, when the sample's residual stress is constant, demagnetizing factor largely determines its magnetic properties. (c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.